An examination of within-session responding following access to reinforcing stimuli. (January 2016) - Rispoli, Mandy; O'Reilly, Mark; Lang, Russell; Machalicek, Wendy; Kang, Soyeon; Davis, Tonya; Neely, Leslie
Highlights: We compared presession satiation and presession restriction to the tangible maintaining challenging behavior for three children. Presession satiation led to subsequent decreases in challenging behavior during instruction as compared to presession restriction. Effects of the presession satiation on challenging behavior maintained for 60 min post intervention. Abstract: Previous research has shown tangibly maintained challenging behavior can be temporarily decreased by providing presession access to the relevant tangible. However, the duration of this beneficial effect is unknown. We measured the subsequent duration of behavior reduction effects following presession access during extended classroom observation sessions by analyzing within-session patterns of responding in three children with autism. An alternating treatments design was used to analyze within- and across-session responding following presession access and presession restriction conditions. The cumulative frequency of challenging behavior was higher following the presession restriction condition for all participants and lower following presession access. Within-session analysis revealed the same basic pattern of responding across participants. Specifically, the first half of the sessions contained very little, if any, challenging behavior; however, after 60 min, the rate of challenging behavior began to increase rapidly for two of the three participants. Results are discussed in terms of implications for practitioners, satiation, habituation, and behavioral contrast.